Basilar artery occlusion in a child treated successfully with mechanical thrombectomy using ADAPT. (13th April 2016) - Lena, Jonathan; Eskandari, Ramin; Infinger, Libby; Fargen, Kyle M; Spiotta, Alejandro; Turk, Aquilla; Turner, Raymond D; Chaudry, Imran
Abstract : Acute ischemic stroke (AIS) in the pediatric population is rare. Furthermore, it is common for physicians to take significantly longer diagnosing a posterior circulation stroke in a child than in an adult. There are increasing case reports in the literature of treating AIS in children with intravenous tissue plasminogen activator, intra-arterial thrombolysis, and/or mechanical thrombectomy. We present the first case of pediatric AIS treated using a direct aspiration first pass technique (ADAPT) as a means of mechanical thrombectomy.